Photoanodes based on TiO2 and α-Fe2O3 for solar water splitting - superior role of 1D nanoarchitectures and of combined heterostructures - Kment, Stepan; Riboni, Francesca; Pausova, Sarka; Wang, Lei; Wang, Lingyun; Han, Hyungkyu; Hubicka, Zdenek; Krysa, Josef; Schmuki, Patrik; Zboril, Radek (Chemical Society reviews, 2017)
Solar driven photoelectrochemical water splitting (PEC-WS) using semiconductor photoelectrodes represents a promising approach for a sustainable and environmentally friendly production of renewable energy vectors and fuel sources, such as dihydrogen (H2). In this context, titanium dioxide (TiO2) and iron oxide (hematite, α-Fe2O3) are among the most investigated candidates as photoanode materials, mainly owing to their resistance to photocorrosion, non-toxicity, natural abundance, and low production cost. Major drawbacks are, however, an inherently low electrical conductivity and a limited hole diffusion length that significantly affect the performance of TiO2 and α-Fe2O3 in PEC devices. To this regard, one-dimensional (1D) nanostructuring is typically applied as it provides several superior features such as a significant enlargement of the material surface area, extended contact between the semiconductor and the electrolyte and, most remarkably, preferential electrical transport that overall suppress charge carrier recombination and improve TiO2 and α-Fe2O3 photoelectrocatalytic properties. The present review describes various synthetic methods and modifying concepts of 1D-photoanodes (nanotubes, nanorods, nanofibers, nanowires) based on titania, hematite, and on α-Fe2O3/TiO2 heterostructures, for PEC applications. Various routes towards modification and enhancement of PEC activity of 1D photoanodes are discussed including doping, decoration with co-catalysts and heterojunction engineering. Finally, the challenges related to the optimization of charge transfer kinetics in both oxides are highlighted.